Recommended Readings for Elżbieta z Radziwiłłów Mielecka by Catholic Preachers in 1579-1581 - Sitkowa, Anna (Melusine. Old Literature and Culture, 2024)
The article discusses prints published between 1579 and 1581, which were specifically addressed to Elżbieta z Radziwiłłów Mielecka (1550-1591). Her religious explorations (having been born into Catholicism, she moved through Calvinism and judaizing circles of Arianism) led her and her husband Mikołaj (d. 1585) to become the focus of efforts aimed at persuading her to return to the Catholic Church by the 1560s. The recommended books were intended to influence her final decision to convert (e.g. Piotr Skarga’s “Żywoty świętych” [“Lives of the Saints”], 1579), and after her confession of Catholic faith in June 1580, to provide guidance for her new religious path (e.g. S. de Moraes’s “O żywocie i śmierci najaśniejszej księżnej parmeńskiej” [“On the Life and Death of the Most Illustrious Duchess of Parma”], 1581) and to encourage her to abandon independent Bible reading (e.g., H. Powodowski’s “Skarbnica Biblijej świętej” [“Treasury of the Holy Bible”], 1581).